Hegemoni Amerika Serikat Terhadap Arah Kebijakan Arab Saudi dalam Konflik Yaman Pasca Arab Spring 2011-2017 - Firmanda Taufiq; Lalu Wahyu Putra Utama (Jurnal ICMES, 2017)
This article aims to analyze the hegemony of the United States against thedirection of Saudi policy in the Yemeni conflict. Historically United States andSaudi Arabia have a close relationship since 1940’s. The relationship is based oneconomic, political, military and security interests. With US support, Saudi Arabiahas a major influence in the Middle East. The research question in this paper iswhat is the reason of Saudi’s attack toward Yemen and what is the role of UnitedStates in this aggression. The theory used in this study is the theory of hegemonywhich is trying to explain how a country controlled other countries politically andeconomically. The study finds that Saudi Arabia’s foreign policy toward Yemen isone of the effect of American hegemony.